Effectiveness of disease management program for hypertension: expert evaluation (Bangladesh Journal of Medical Science, 2025)
Background Hypertension is a risk factor for cardiovascular disease and premature mortality worldwide. Effective management of this condition requires the integration of structured interventions, such as disease management programs, which have proven clinically significant in increasing treatment adherence and improving patient outcomes. Objective To evaluate the effectiveness of a disease management program in achieving target blood pressure in primary care. Materials and methods A retrospective random sampling method was used to include 200 medical cards (form 025/u) of patients with arterial hypertension registered for dispensary care in 4 city polyclinics of Astana, Kazakhstan, for 2023-2024. Patients were divided into two groups depending on whether they achieved the target BP level (